Male circumcision as HIV prevention in Africa - (:unkn) unknown (My University, 2011)
While the practice of male circumcision (MC) is declining in Western countries, its promotion in order to prevent HIV/AIDS is currently implemented in Eastern and Southern Africa, where it is not frequently carried out and where the HIV epidemic is very widespread. However, in spite of the scientific demonstration of MC's efficacy, its advocacy as a method to prevent HIV/AIDS has generated controversy, with its most extreme opponents denouncing a conspiracy by an occult organisation of powerful "circumcisers". Drawing on an analysis of scientific papers and the responses they have elicited in the journals where they are published and on Internet sites, this article sheds light on this opposition and its connotations. It situates the distorted vision of Africans and of their sexuality - as expressed through these publications and reactions - in a post-colonial context where the ex-colonisers' domination over ex-colonised populations is perpetuated under different forms. Finally, it analyses the action designed in Western countries and exerted on African bodies as an instance of biopower involving medical experimentation transfers to Southern countries. When deprived of any symbolic dimension and practised with a prophylactic objective, MC appears emblematic of such biopower.
Keywords: African Research